A novel experimental apparatus for the study of low temperature regeneration CO2 capture solvents using hollow fibre membrane contactors. (November 2018) - Simons, Tristan J.; Hield, Peter; Pas, Steven J.
Graphical abstract: Highlights: A novel CO2 capture apparatus has been constructed and is described in detail. Batch and continuous CO2 capture/regeneration is demonstrated for a protic ionic liquid. Low temperature regeneration of CO2 is shown on a hollow fibre membrane contactor. Abstract: The design, capability and construction of a novel, experimental apparatus for the study of low temperature regeneration CO2 capture agents is presented. The decisions and challenges in developing a new experimental capability are discussed, as well as how it addresses the experimental intermediate between bench scale experiments and large, application specific projects. To demonstrate the utility and capability of the apparatus, a low temperature regenerating CO2 capture protic ionic liquid (PIL) solution – dimethylpropylenediamine acetate + 50% H2 O – was used to remove CO2 from an incoming gas stream consisting of 10% (v/v) CO2 in air. SuperPhobic ® 2.5 × 8 hollow fibre membrane contactors were used for both the absorption and regeneration processes. The loading-only experiment achieved pseudo steady state in approximately 12 min, achieving a pseudo steady-state mass transfer rate (Koverall ) of (3.66 ± 0.2) × 10 −5 m s −1, and a CO2 removal rate of 5.15 × 10 −3 g m −2 s −1 . This value is comparable to other ionic liquid CO2 capture agents such as 1-ethyl-3-methylimidazolium ethylsulfate that have also been measured under pseudo-steady state conditions. In continuous operation, where CO2 is absorbed and stripped in series, steady-state was achieved in approximately 15 h. Due to the higher concentration of CO2 in the liquid under steady-state conditions, the value of Koverall decreased to (1.80 ± 0.1) × 10 −5 m s −1, with a CO2 removal rate of 2.89 × 10 −3 g m −2 s -1 . The effects of several parameters on the steady-state CO2 capture rate, namely vacuum pressure of regeneration and liquid flow through the contactor were studied. Several factors were found to affect the stability of the overall CO2 removal rate, including H2 O loss from the aqueous solution. With the utility and flexibility of the designed system, we have demonstrated that PILs are certainly worthy of further investigation as CO2 capture agents for a range of applications.